Independence day - Enmerich, Ronald (b, 1999)
One of the biggest box office hits all time delivers the ultimate encounter when powerful aliens launch an invasion against the human race. The spectacle begins when massive spaceship appear. Wonder turns to terror as the ships blast destructive beams of fore down cities all over the planet. Now the world's only hope lies determine survivors, uniting for one last strike against the invader - - before it's the end of mankind